Synopsis of the Piro world: Ethics and aesthetics in Piro art. Modifications in the Piro kinship structures during the rubber boom (1885-1915). The Piros settlements and the persistence of their identity - Román Villanueva, Luis (1985)
The three articles that we present below aim to detail three fundamental aspects of the Piro culture. This ethno-linguistic group, belongs to the Arahuaca family, like the Campa, Machiguenga and Amuesha, it is located mainly on the banks of the Urubamba river belonging to the Echarate district, La Convencion Province, Cusco Department and the Sepahua District , Atalaya Province, Ucayali Department. The estimated population for this group is 1600 inhabitants (Wise, M.R. 1972) which is distributed in 12 native communities, of which half are titled by the Peruvian State. There is regular bibliography on this group, mainly with regard to linguistics, stories of travelers and missionaries of various orders, and to a lesser extent ethnographic and ethno-historical works. In this series of articles the authors seek a detailed approach to deepen the knowledge of this ethnic group. For this we will use the previous works to which we will add our notes and appreciations collected during four years of work in the area. The first article by L. Komán tries to explain the relationship between the ideological and the aesthetic, for which reference is made to mythology and the aesthetic manifestations of the Pyro group. In the second article, the same author points out a structural transformation in the Pyro kinship system during the rubber exploitation boom, giving rise to a variation of the original model, which guarantees the biological and cultural reproduction of the group. V. de Szyzslo's final article describes the way in which each of the families of the Miaría pyre community, in the Urubamba, has the space to build their homes and communal premises. The three articles are therefore complementary to obtain a detailed view of the ideological, socio-political and technological aspects that make up the Piro universe.